SENG OKSIDA (ZnO) SEBAGAI FOTOKATALIS PADA PROSES DEGRADASI SENYAWA BIRU METILEN - Syukri Darajat; Hermansyah Aziz; Admin Alif (Universitas Andalas, 2008)
ABSTRACT A research aimed to study the influence of ZnO white powder on photodegradation of methylene blue using Merkuri lamp (l = 365 nm) as light source have been reached. A suspension of ZnO (40 mg) mixed with 25 mL of methylene blue solution (initial concentration of 0.015 mM) then was illuminated for 60 minutes showed degradation and quantum yield amounting 23.84% and 3.55 molecules photon-1, respectively. These results mean that by using ZnO as photocatalyst there is about four times efficiency than the one without ZnO either in case of time consumed or the number of photon applied. In kinetic study, it has been observed that such semiconductor-catalyzed photochemical reaction obeys the first order rule where rate constant and half time consecutively were 0.0029 minute-1 and 231 minutes. Keywords : photodegradation, photocatalyst, quantum yield, semiconductor, photochemical reaction.